A study of environmental impact of air pollution on human health: PM deposition modelling - A. Gandhimathi; R. Manju; K. Ramadevi; S. Rajalakshmi; I. Mayilvahanan (Glob. Nest. J., 2023)
Earth is comprised of land, air and water. Air contains oxygen, nitrogen, carbon dioxide, water vapor, and other gases are present above the permissible limit, and it creates effects on human health. It is one of the most important public health issues due to the development of urbanization, industrialization, and globalization in large cities. Air pollution levels in developed countries have been increasing in recent years. In developing countries air pollution levels are still high. In recent years, health studies have become visible showing harmful health effects in lungs and respirable system. Air pollution is responsible for 7 million deaths annually. It affects the health of humans and other living beings in our world. The government has developed the guidelines for air quality and rule to restrict emissions in effort to control air pollution. These updated AQGs provide exact guidelines for PM10 and PM2.5. The primary objective of this paper is to study ambient air quality and its impact on lungs. Particulate matter are the particles suspended in air/atmosphere. Mainly PM10 and PM2.5 Ultra fine particles (<1 mu m) are mainly responsible for causing interruption for human health.PM10 and PM2.5 are characterized by their presence only within the upper respiratory tract. Some PM2.5 and ultra-fine particles are characterized by their presence of deeper regions of alveoli. Ultrafine particles (PM0.1), which are present in the air in large numbers, pose a health risk. They generally enter the body through the lungs but translocation to essential organs. Compared to fine particles (PM2.5), They cause more pulmonary inflammation and are retained longer in the lung. Their toxicity is increased with smaller size, larger surface area, adsorbed surfacematerial, and the physical characteristics of the particles. Exposure to PM0.1 induces cough and worsens asthma. Metal fume fever is a systemic disease of lung inflammation most likely caused by PM0.1. The disease is manifested by systemic symptoms hours after severe exposure to PM0.1 could cause systemic inflammation, endothelial dysfunction, and coagulation changes that predispose individuals to cardiovascular disease and hypertension.
Keywords: Noise maps; Sleep disturbance; Mean awareness index score